1995
DOI: 10.1242/jcs.108.5.2109
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sequestration of DPP IV/CD26 and other cell surface proteins in an autophagic-like compartment in Caco-2 cells treated with forskolin

Abstract: The enterocytic differentiation of Caco-2 cells, a human colon adenocarcinoma cell line, is accompanied by the transcriptionally regulated expression of a subset of proteins and their correct sorting towards the cell surface. In the present work we have explored the possibility that post-translational events may interfere with this process by investigating the short term effects of a potent adenylyl cyclase activator, forskolin, on cell surface expression of dipeptidyl peptidase IV. Previous works have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 76 publications
0
1
0
1
Order By: Relevance
“…Dans les cellules hépatiques, la DPP IV est adressée en totalités au pôle basolatéral et rejoint le pôle apical par transcy tose (3). Dans les cellules Caco-2, d'origine intestinale, le trafic de la protéine est mixte avec environ 30-40 % de la protéine arrivant au pôle apical par voie directe le reste par transcytose (2,25,34). L'analyse plus détaillée de la situation indique cependant qu'il ne faut pas cari caturer ces caractéristiques de trafic.…”
Section: éTude Du Trafic D'une Hydrolase Particulière La Dpp IVunclassified
“…Dans les cellules hépatiques, la DPP IV est adressée en totalités au pôle basolatéral et rejoint le pôle apical par transcy tose (3). Dans les cellules Caco-2, d'origine intestinale, le trafic de la protéine est mixte avec environ 30-40 % de la protéine arrivant au pôle apical par voie directe le reste par transcytose (2,25,34). L'analyse plus détaillée de la situation indique cependant qu'il ne faut pas cari caturer ces caractéristiques de trafic.…”
Section: éTude Du Trafic D'une Hydrolase Particulière La Dpp IVunclassified
“…The brush-border hydrolase DPP4 is a type II transmembrane protein. It is heavily modified with N- and O-linked glycans in its extracellular domain ( Misumi et al, 1992 ; Baricault et al, 1995 ; Fan et al, 1997 ), which have been suggested to be critical apical sorting determinants of DPP4 ( Alfalah et al, 2002 ). Even though several studies have suggested diverse trafficking routes for DPP4, the mechanisms and protein machineries underlying these processes remain enigmatic so far ( Casanova et al, 1991 ; Baricault et al, 1993 ; Low et al, 1992 ; Sobajima et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%